UNDERSTANDING THE CONCEPT OF SCIENCE IN THE MODERN ERA - Tanjung, Fadhilah Sukmawati; Sumarna, Elan; Surahman, Cucu (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This study aims to examine the meaning and relevance of the hadith of Abu Dawud No. 3641 about the virtue of knowledgeable people in facing the challenges of education in the modern era that tends to be pragmatic and materialistic. This study is a qualitative study with the method of library study and tahlīlī analysis. Primary data were obtained from the book of Sunan Abu Dawud, while secondary data came from related books and articles. This study analyzed the sanad and matan of the hadith in depth to ensure its validity. The results of the study show that the sanad of this hadith is muttaṣil (connected) with most of the narrators who are considered thiqa, although there are narrators who are ḍa'īf (weak) so that this hadith is classified as hasan lighairihi and can still be used as an argument. This hadith analogizes the virtue of knowledgeable people like the full moon that illuminates the stars in the sky. The meaning is that knowledgeable people have a broad impact on society compared to worshipers whose benefits are individual. This research contributes to strengthening understanding of the importance of education based on religious values ​​in the midst of modernization, and recommends the integration of religious knowledge and general knowledge to shape the noble morals of students.